2010
DOI: 10.1002/jobm.200900113
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase regulates heavy metal sensitivity, bikaverin production and plant tissue colonization in Fusarium proliferatum

Abstract: A homologue of the adenylyl cyclase (AC) gene of Neurospora crassa, named Fpacy1 was cloned from the genomic library of Fusarium proliferatum ITEM 2287 by screening the library with a DNA fragment amplified by using PCR primers designed from conserved sequences of the catalytic domain of AC genes from other fungi. The deduced FPACY1 protein had 53-77% identity with the AC proteins of other fungi. DeltaFpacy1 mutants obtained by targeted gene disruption showed retarded vegetative growth, increased conidiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 51 publications
4
40
0
Order By: Relevance
“…Thus, only F. fujikuroi C1995 produces GAs and fusarins at detectable levels, while only F. proliferatum D4854 produces fumonisin B 1 and fusarubins under the investigated conditions. Both strains produce small amounts of bikaverin, a red pigment typical for species of the GFC (Wiemann et al, 2009;Kohut et al, 2010), while we found high amounts of the fusarubins, a second group of red pigments, in F. proliferatum D4854 (Fig. 4).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, only F. fujikuroi C1995 produces GAs and fusarins at detectable levels, while only F. proliferatum D4854 produces fumonisin B 1 and fusarubins under the investigated conditions. Both strains produce small amounts of bikaverin, a red pigment typical for species of the GFC (Wiemann et al, 2009;Kohut et al, 2010), while we found high amounts of the fusarubins, a second group of red pigments, in F. proliferatum D4854 (Fig. 4).…”
Section: Discussionmentioning
confidence: 82%
“…Due to the significantly different production capacity of fusarubins between the parental strains, fusarubins, rather than bikaverin, were analyzed in the progeny. Previously, a red pigment produced under acidic conditions in another F. proliferatum strain was described as bikaverin based solely on spectrofluorimetric measurements (Kohut et al, 2010). It would be interesting to perform more precise HPLC and MS analyses to determine whether the analyzed pigment was bikaverin or fusarubins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in N. crassa demonstrated that cAMP signaling and HOG1 MAPK signaling play opposite role in respect to oxidative stress response: disturbances in the cAMP and the HOG1 pathways result in increased and decreased H 2 O 2 tolerance, respectively. In F. proliferatum and F. verticillioides, disruption of Acy1, the adenylyl cyclase gene resulted in enhanced resistance to heat shock and oxidative stress (Kohut et al, 2010;Choi and Xu, 2010). However, in contrast to these data, the acyAmutants of F. fujikuroi MP-C were more sensitive to H 2 O 2 than the wild type .…”
Section: Sensitivity Of Different Fusarium Species To Hydrogen Peroxidementioning
confidence: 80%
“…On the contrary, fumonisin B1 production was not regulated by cAMP signaling either in F. proliferatum (Kohut et al, 2010) or F. verticillioides (Choi and Xu, 2010). This signaling route regulates, however negatively regulates the production of bikaverin, another polyketide metabolite in Fusarium species (Kohut et al, 2010;Choi and Xu, 2010;García-Martínez et al, 2011). Moreover, the production of another secondary metabolite such as carotenoids is upregulated in Fusarium species not only by cAMP signaling (García-Martínez et al, 2011) but other regulatory elements related to sexual reproduction (Ádám et al, 2011).…”
Section: The Role Of Mapk Pathways In Secondary Metabolism Of Fusariumentioning
confidence: 85%
See 1 more Smart Citation